Factors influencing consumers’ attitudes and the moderating role of social influence in the banking industry - Tanchangya, Tipon; Al Mamun, Mohammad Abdullah; Akter, Tania; Hossain, Balayet; AbdulBaten, Abul Khair Mohammed; Islam, Naimul; Alam, Md Karimul (Discover, 2025)
It is now more important to comprehend customer attitude as digital transformation changes financial services around the world, particularly in hybrid banking environments. This research identifies the key factors reshaping consumers’ attitudes and consumer behavioural intention within the Bangladeshi banking sector. The investigation also employs consumers’ attitudes as mediators to examine the indirect impact of independent variables on consumers’ behavioural intentions. Furthermore, the research also seeks the moderating role of social influence (SI) on the relationship between consumers’ attitudes and consumer behavioural intentions. Partial least squares structural equation modelling (PLS-SEM) was applied to empirically analyse 398 fintech service users’ responses. The research found that perceived usefulness (PU), perceived ease of use (PEU), perceived financial risk (PFR), and perceived security risk (PSR) have a direct, significant impact on consumers’ attitudes. Consumers’ attitudes are also positively correlated with consumer behavioural intention. Consumers’ attitudes reveal a significant mediating relationship between PU, PEU, and consumer behavioural intention, but no mediation role between PFR, PSR, and consumer behavioural intention. Additionally, SI positively moderated the relationship between consumers’ attitudes and consumers’ behavioural intentions in the banking industry. This research provides insights for policymakers and stakeholders to develop new policies, mitigate risk, and enhance customer satisfaction to make them loyal to financial services. The study also sheds light on the customers’ attitudes so that managers of the banks pay attention to the concentration of consumer needs and provide feedback to make loyal customers.